Diagnosis of Kikuchi-Fujimoto disease in an 11-year-old girl with fever and sickle cell disease. Issue 8 (24th August 2020) - Cannon, Laura; Wang, Endi; Becker, Mara
Abstract : Kikuchi-Fujimoto disease (KFD) is a rare lymphohistiocytic disorder which can cause prolonged fever and other systemic B symptoms including diffuse lymphadenopathy. Given its clinical presentation, there is often initial concern for lymphoma and diagnosis requires lymph node biopsy. It most frequently affects young women of Asian descent; it is less commonly encountered in paediatric patients. KFD is typically a benign, self-limited process, however, there is an association with development of systemic lupus erythematosus. Given its rarity, it remains unclear if KFD is associated with other chronic conditions. Here we present the third case of KFD occurring in a paediatric patient with sickle cell disease.